1985
DOI: 10.1021/bi00329a037
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian chymotrypsin-like enzymes. Comparative reactivities of rat mast cell proteases, human and dog skin chymases, and human cathepsin G with peptide 4-nitroanilide substrates and with peptide chloromethyl ketone and sulfonyl fluoride inhibitors

Abstract: The extended substrate binding sites of several chymotrypsin-like serine proteases, including rat mast cell proteases I and II (RMCP I and II, respectively) and human and dog skin chymases, have been investigated by using peptide 4-nitroanilide substrates. In general, these enzymes preferred a P1 Phe residue and hydrophobic amino acid residues in P2 and P3. A P2 Pro residue was also found to be quite acceptable. The S4 subsites of these enzymes are less restrictive than the other subsites investigated. The sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(98 citation statements)
references
References 39 publications
6
91
1
Order By: Relevance
“…A previous study in which a benzyl thioester substrate was compared with its p-nitroanilide counterpart (SucVal-Pro-Phe-S-Bzl versus Suc-Val-Pro-Phe-NH-Np) [23] found that the thioester was 10-times more reactive than the p-nitroanilide with human skin chymase and 171-times more reactive with cathepsin G, a result broadly in accord with the findings presented here. As reported previously [24], cathepsin G was found to be more sensitive than chymase to inhibition by aprotinin.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study in which a benzyl thioester substrate was compared with its p-nitroanilide counterpart (SucVal-Pro-Phe-S-Bzl versus Suc-Val-Pro-Phe-NH-Np) [23] found that the thioester was 10-times more reactive than the p-nitroanilide with human skin chymase and 171-times more reactive with cathepsin G, a result broadly in accord with the findings presented here. As reported previously [24], cathepsin G was found to be more sensitive than chymase to inhibition by aprotinin.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies, utilizing peptide 4-nitroanilide substrates, indicated that substrates with a Phe residue at the P, position are preferentially cleaved by RMCP-1 (Powers et al, 1985). Our results, identifying the PhelG-GlylF bond in thrombin as a target for RMCP-1, are thus in agreement with these observations.…”
Section: Discussionsupporting
confidence: 92%
“…The corresponding peptide was synthesized, and this substrate was hydrolyzed 40 times more efficiently than S-2586 in the presence of heparin. When comparing the results in the phage display analysis of rMCP-4 with the substrate specificity analysis for rMCP-2 performed by Powers et al (8), several features of these enzymes were shown to be shared. The most preferred P3 amino acid for rMCP-2 was shown to be Val, followed by Leu, Met, Thr, and Phe, a result that correlates well with the phage display result for rMCP-4.…”
Section: Expression Purification and Analysis Of Recombinant Rmcp-4 -mentioning
confidence: 96%
“…rMCP-5 (initially designated as rMCP-3) is the rat ␣-chymase and the homologue to the single human chymase found so far. The rat mast cell ␤-chymases rMCP-1 and rMCP-2, expressed by connective tissue mast cells and MMC, respectively, have been extensively investigated with regard to tissue distribution, charge, heparin binding, substrate specificity, inhibitor susceptibility, and structure (7)(8)(9)(10). Recent data suggest that MMC mediators, in particular rMCP-2, directly induce physiological changes in the gastrointestinal tract, such as an increase in epithelial permeability (11).…”
mentioning
confidence: 99%